Development of Teaching Media of Multiplication Ketupat (Ketupel) on Improving The Ability to Count Multiplication of Grade III Elementary School Students - Dimas Anggereksa; Ima Mulyawati (Eduvest - Journal of Universal Studies, 2024)
Ketupel media is a media developed, using board material with a size of 40 cm x 40 cm and in the form of a diamond that raises local wisdom in the month of Ramadan. This research aims to develop teaching media for multiplication ketupat (Ketupel) on the ability to count multiplication of third grade elementary school students. The research subjects are third grade elementary school students. The type of research to be conducted is research and development (R&D). The development model of this research is the ADDIE development model, namely Analysis, Design, Development, Implementation, Evaluation. At the planning stage, interactive media was designed using Ketupel media. After completion of the design, it was validated by material experts and media experts. The results of the material experts obtained 92% with valid criteria, while the media experts obtained 92% with valid criteria. After the media is declared valid then the media is implemented on grade III elementary school students, with the results of the N-gain Score of 66% indicating that the media is quite effective in use. And the results of student questionnaires after implementation with 95% results show the media is very interesting. It can be concluded that Ketupel Media can improve students' multiplication counting skills.